Wide-Awake Local Anesthesia With no Tourniquet Versus General Anesthesia for the Plating of Distal Radius Fracture: A Systematic Review and Meta-Analysis - Tu, Ting-Yu; Hsu, Chih-Yang; Lin, Pei-Chin; Chen, Chun-Yu (Frontiers in Surgery, 2022)
Abstract Background: Distal radius fractures are treated using open reduction and internal fixation and using general anesthesia (GA) or regional blocks. A new technique, wide-awake local anesthesia with no tourniquet (WALANT), allows this operation to be conducted in nonsedated patients without the use of tourniquets. Objective: We analyzed whether WALANT yields better outcomes than GA in the treatment of patients with distal radius fractures. Evidence Review: We searched the PubMed, Cochrane Library, Embase, and Scopus databases for cases of distal radius fractures treated using WALANT or GA. The outcomes of interest were duration of preparation for surgery, duration of surgery, blood loss, and length of postoperative hospitalization; visual analog scale (VAS), Mayo wrist score, and Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) questionnaire score on postoperative day 1; range of motion (ROM); time until bone union; and complication rate. Findings: We systematically reviewed 4 studies with a total of 263 patients (128 with WALANT and 135 with GA). In comparison with GA, WALANT required less time for preparation for surgery, shorter postoperative hospitalization, and lower postoperative day 1 VAS scores; however, blood loss was greater. Functional outcomes (ROM, QuickDASH score, and Mayo wrist score), complication rates, and times until union did not differ considerably between the two methods. Conclusion: The included studies demonstrated that durations of preparation for surgery and postoperative hospitalization were shorter and pain on postoperative day 1 was less severe with WALANT than with GA. Although blood loss in surgery was greater with WALANT, this technique is a novel and promising alternative to GA.